Pengaruh Waktu Thawing Terhadap Kualitas Spermatozoa Ayam Buras: The Effect of Thawing Time on the Quality of Native Chicken Spermatozoa - Siska Milanda; Abdul Hakim Fattah (Anoa: Journal of Animal Husbandry, 2022)
The purpose of this study was to determine the effect of thawing time on the quality of native chicken spermatozoa. The research design used in this study was a completely randomized design (CRD) with 5 treatment levels and 5 replications. The treatments used were P1 = thawing time of 20 seconds, P2 = thawing time of 30 seconds, P3 = thawing time of 40 seconds, P4 = thawing time of 50 seconds, P5 = thawing time of 60 seconds. Semen that has been diluted to be packed in 5 ministraw 0.25 ml, then equilibrated for 2 hours. After equilibration, proceed with the freezing process (prefreezing). Then the straws were stored in a liquid N2 container (-196°C) for 24 hours. frozen semen was thawed again with warm water at 37°C according to the treatment. Parameters observed were sperm motility and recovery rate. The results of this study showed that thawing time had no significant effect (P>0.05) on sperm motility and recovery rate. It was concluded that the thawing time of 20 to 60 seconds could be used in freezing native chicken semen.